LEARNING ONE-DIGIT DECIMAL NUMBERS BY MEASUREMENT AND GAME PREDICTING LENGTH - Astuti, Puji (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
This paper aims to describe how students develop understanding of one-digit decimals. ToÃ‚Â achieve the aim, Local Instruction Theory (LIT) about the process of learning decimals and theÃ‚Â means designed to support that learning are developed. Along with this idea, the framework ofÃ‚Â Realistic Mathematics Education (RME) is proposed. Based on the aim, design researchÃ‚Â methodology is used. This paper discusses learning activities of three meetings from teachingÃ‚Â experiment of the focus group students of the fourth grade elementary school in Surabaya:Ã‚Â SDIT Al Ghilmani. The data indicated that the learning activities promoted the studentsÃ¢â‚¬â„¢Ã‚Â understanding of one-digit decimal numbers.Keyword: measurement, decimal numbers, number lineÃ‚Â DOI: http://dx.doi.org/10.22342/jme.5.1.1447.35-46